Bacterial sinusitis: a striking complication report - Joana Cascais Costa; Catarina Lucas (Sociedade Galega de Medicina Interna, 2017)
Introduction: Sinusitis is the translation of the inflammatory process of the mucous membranes of the paranasal and nasal sinuses, being able to reach several locations simultaneously. It is often associated with respiratory infections and the causative agents are aerobic agents, namely Streptococcus pneumomiae and Haemophylus influenzae. Currently, the complications of bacterial sinusitis are rare and when they occur they are related to the local extension of the infectious process, to the central nervous system, orbit or to the orbital tissues. Clinical case: A 53-year-old female patient with a history of dilated cardiomyopathy who had recourse to the Urgency Service due to odynophagia, pain and facial flushing, with drainage of purulent secretions through the left nasal cavity, With a month of evolution. She was a patient with a recent hospitalization in the Intensive Care Unit (ICU) due to septic shock secondary to right pneumonia. On arrival in the urgency, the patient had a clinical picture compatible with septic shock. Exuberant inflammatory signs were identified in the left hemiface and purulent rhinorrhea. The lesions of gangrene on the 3rd, 4th and 5th toes of the left foot were also observed, and septic embolization was suspected. She underwent encefalic tomography scan that showed sinusitis of the sinuses on the left side, conditioning facial and periorbirtary cellulitis, without other alterations. Angio-TC of lower limbs had no changes. Established antibiotic therapy with meropenem and vancomycin. The patient underwent surgical drainage of the inflammatory processes. The 4 blood cultures performed isolated Staphylococcus hominis. CONCLUSIONS: The clinical case presented is of particular interest, both for severity and for the unexpected complication of a case of sinusitis - septic embolization to condition gangrene of several left toes, in patients with multiple comorbidities, and recent ICU hospitalization .